Reusable Block AES: A Modified AES Algorithm for the Encryption and Decryption of Sensitive Data - Hussain Sikder, Md Irfan; Sarker, Proshenjit; Hasan, Md Tariq; Ismat Kadir, Mohammad (2025 International Conference on Electrical, Computer and Communication Engineering (ECCE), 2025)
In data communication and storage, information is stored in various formats, such as documents (TXT, PDF, DOC) and images (JPG, PNG, JPEG). Critical sectors, including airports, police stations, medical centers, and document storage facilities, require secure data encryption and reliable recovery methods. While existing encryption systems can recover text and grayscale images, they often fail with multiple formats and may cause data loss in color images, which is a significant risk. Our system, built on the universally accepted Advanced Encryption Standard (AES) algorithm, addresses these issues by providing fully recoverable encryption and decryption, enhanced by a reusable block technique that increases speed and maintains data integrity. This approach ensures fast and complete recovery of diverse data types, including documents, images, Electrocardiogram (ECG) signals, and e-prescriptions, without compression. Our system outperforms standard AES, offering 100% accurate data recovery across multiple formats, and has been successfully applied in critical sectors such as telehealth and telemedicine, improving data security and performance.